A trial patch to the extracurricular perspective of sustainable development program in elementary schools of Turkey - ŞEKER, Fatih; AYDINLI, BAHATTIN (Springer Science and Business Media LLC, 2021)
Abstract
Sustainable development (SD) and science education have become interwoven categorical issues under the name of science education for sustainable development (SESD). Education can play a crucial role in merging the dimensions of SD as ecology, economy, and energy, along with society in a united holistic goal. Furthermore, it can provide the necessary motivation and self-fulfillment for individuals and communities. Extracurricular activities should also be implemented along with formal ones in courses that are related to socio-scientific issues like SD. In line with this perspective, this study mainly aims to find new means of developing an extracurricular module program based on the principles of SD, in order to address the defects, deficiencies, and needs in science education around the world. For the sake of these, the module program was constructed kneading concepts of energy transformations, biodiversity, and narrating socio-scientific problems that would foster positive student decision-making on SD issues. The study also aims to examine whether the SESD module program would have a significant effect on the academic success and opinions regarding SD of primary school students in science lessons. The study sample comprised 92 Turkish fifth-grade students. A mixed method was handled by allowing qualitative and quantitative research methods in the same context. Qualitative and quantitative data analysis revealed that the SESD module program significantly affected fifth-grade students in terms of their knowledge and opinions to increase their willingness to take action and responsibility.
Keywords: 4. Education; 11. Sustainability; 12. Responsible consumption